Overview of health issues in school-aged children with down syndrome - Thomas, K.; Girdler, Sonya; Bourke, J.; Deshpande, A.; Bathgate, Katherine; Fehr, S.; Leonard, H. (2010)
Background: School-aged children with Down syndrome experience an array of medical conditions and health care problems. Although there have been vast improvements in the medical management of these conditions, they still significantly impact on quality of life for families and children with Down syndrome. However, despite the magnitude of this problem limited literature has described the overall health status of children with Down syndrome.Aim: The purpose of this review was to describe the medical conditions commonly experienced by school-aged children with Down syndrome and to consider the clinical implications of this knowledge.Methods: Electronic searches of Medline, CINAHL, and PsychINFO and manual searches of reference lists identified relevant articles from 1990 to 2009. Studies were included if the topic involved one or more medical comorbidity and participants were children aged 18 years or younger with a diagnosis of Down syndrome. Articles were excluded at the title or abstract level if they were not peer-reviewed, in a language other than English, or did not meet the inclusion criteria. A narrative review of this research was possible.Results: Common medical conditions experienced by school-aged children with Down syndrome include: heart disease; respiratory problems; gastrointestinal disorders; obesity; ophthalmological, ear, and hearing problems; musculoskeletal problems; leukemia and thyroid conditions; frequent infections; and dental disease. Prevalence estimates for these conditions varied depending on the diagnostic criteria or study methodologies. © 2010 Elsevier Inc.